Management of massive gastrointestinal haemorrhage. Issue 10 (October 2019) - Mackenzie, Paul D.; Rogers, Matthew; Gallagher, Michelle; Rockall, Timothy
Abstract: Acute gastrointestinal bleeding is a common medical emergency, accounting for approximately 85, 000 admissions in the United Kingdom per annum. It is associated with significant morbidity and mortality. GI haemorrhage is commonly categorized according to source of blood loss; either upper GI (above the ligament of Treitz) or lower GI (below the ligament of Treitz). Rapid assessment, resuscitation and correction of coagulopathy should be undertaken to stabilize the haemodynamically compromised patient and definitive intervention should not be delayed. Clinicians may use of a range of treatment modalities, including endoscopic and interventional radiological techniques in order to get control of haemorrhage, which should be tailored to the site of bleeding and pathology. Where control is not achieved the clinician should consider either repeat intervention, use of alternative haemostatic techniques or different modalities to achieve haemostasis. Rarely is surgery the chosen treatment modality and surgical intervention should only be undertaken where all other measures to control haemorrhage have failed.